Attitudes towards and mental health during COVID-19 pandemic: An online cross-sectional survey in the State of Goiás, Brazil (Research, Society and Development, 2020)
The novel Corona Virus Disease (COVID-19) has been spreading through all the world fastly leading to a massive public reaction. The knowledge and attitude toward measures for prevention are essential in the control of pandemic infection. Pandemics may contribute to intensified levels of stress, and anxiety is a natural reaction to any stressful situation. This study aimed to assess the knowledge, attitudes towards, anxiety and perceive mental health care among Brazilian Population from Goiás State during COVID-19 pandemic. An online survey was conducted, and a total of 251 responses were received. The participants were older than 18 years, with an average of 33.95. The participants demonstrated a moderate level of knowledge about the COVID-19 infection and its preventive aspects with more than 92% believing that social distance is essential to stop the virus spread and 93.2% agreeing to quarantine or isolate themselves if they present symptoms. Sleep difficulties and distress related to social media were reported in 20.8% and 48.6% of participants, respectively. Most agreed on the need for mental healthcare and assistance from professionals during the pandemic. Our results reflect the need to raise awareness and discuss people's mental health concerns and highlights the urgent need for the government and professional associations be prepared to deal with the psychological effects of the pandemic.